Pengaruh Rasio Profitabilitas, Rasio Leverage, dan Pengungkapan Good Corporate Governance Terhadap Nilai Perusahaan - Sanusi Sanusi; Amir Indrabudiman; Napisah Napisah (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
This research was conducted aimed at analyzing the Influence of Profitability, Leverage, dan Good Corporate Governance is notfacing the Value of the Company. This research was conducted on food & beverage subsector manufacturing companies listed on the Indonesia Stock Exchange for the period 2017-2021. The sample determination method in this study uses the purposive sampling method with a sample of 18 food & beverage subsector manufacturing companies that have met the sample criteria. The study used multiple linear regression analysis techniques and used SEM PLS 3.2.6 statistical test tool. The results of this study Profitability have a positive and significant effect on Company Value, Leverage does not affect company value, Good Corporate Governance has a positive and significant effect on Company Value.